Effect of ethanol on interactions of bitter and sweet tastes in aqueous solutions - Zdeňka PANOVSKÁ; Alena ŠEDIVÁ; Markéta JEDELSKÁ; Jan POKORNÝ (Czech Journal of Food Sciences, 2008)
Experimental samples simulated the composition of vermouths. In all experiments, 0.01% quinine was used as a standard bitter substance. Sucrose increased the acceptability in the concentration range of up to 14%, remaining constant at higher concentrations, both in aqueous and 16% ethanolic solutions. A decrease of bitterness was observed in water but not in 16% ethanol. Ethanol did not affect the sweetness appreciably at the concentrations of up to 16%, but 32% ethanolic solutions appeared less sweet. Ethanol enhanced the bitterness only at high concentrations; interactions were similar in the samples containing 10% and 16% sucrose. Aspartame and Neotame sweetness increased the acceptability and decreased the bitterness similarly to sucrose, both in aqueous and in 16% ethanolic solutions.